Deciphering the hydrodynamics of lipid-coated microbubble sonoluminescence for sonodynamic therapy - Priyankan Datta; Sreejesh Moolayadukkam; Rakesh Prasad Sahu; Ranjan Ganguly; Swarnendu Sen; Ishwar K. Puri (Ultrasonics Sonochemistry)
Sonodynamic therapy (SDT) is a minimally invasive targeted cancer therapy that uses focused low-intensity ultrasound (<10 MPa, <10 W/cm2) to activate sonosensitizer drugs. Once activated, these chemical compounds generate reactive oxygen species (ROS) to damage and kill cancer cells. A Phase I clinical trial has shown promising results for treating glioblastoma with SDT. We hypothesize that the efficacy of SDT can be improved by introducing lipid-coated microbubbles that produce a sonochemical effect that enhances ROS production. We investigate the hydrodynamics of a U.S. Food and Drug Administration (FDA)-approved microbubble, Lumason®, and a phospholipid-coated oxygen microbubble to predict the ultrasound parameters that induce sonoluminescence onset in biophysically relevant medium (e.g., water and blood) under clinical SDT conditions. The threshold pressures and frequencies for sonoluminescence with these therapeutic agents lie between 20 kHz – 1 MHz and 0.05 MPa – 1 MPa, respectively. The lipid-coated oxygen microbubble exhibits stronger sonoluminescence than the Lumason® microbubble, suggesting its use for improving SDT efficacy.